Handbook of polymer-fibre composites (London, 1994)
This book reflects this trend and offers an in-depth and up-to-date examination of fibre-reinforced plastics from both a scientific and a technological perspective. It covers the main subdivisions of the field: fibrous reinforcements for composite materials; polymers and matrices; fabrication of polymer composites; micro- and macromechanical properties of composites; environmental aspects
Keywords: fibrous composites,polymeric composites